2014
DOI: 10.1248/bpb.b13-00635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Chlorogenic Acid on Random-Pattern Dorsal Skin Flap Survival in Diabetic Rats

Abstract: There has been considerable interest in understanding the effects of antioxidants in flap survival during diabetes. Previous studies showed that chlorogenic acid (CGA) exhibits potent antioxidant effects. We aimed to determine the effects of systemic CGA treatment on skin flap survival in an experimental random-pattern dorsal skin flap model in diabetic rats. Twenty-eight male Wistar rats were divided into four groups: phosphate buffered saline (PBS)-treated or CGA-treated nondiabetic rats, PBS-treated or CGA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 49 publications
(87 reference statements)
2
27
0
Order By: Relevance
“…There has been a wide range of dosage for systemic administration of CGA, from 2.5 to 400 mg/kg (Hunyadi et al 2012;Karthikesan et al 2010a, b;Mubarak et al 2012;Yun et al 2012). However, systemic CGA treatment has antiinflammatory, analgesic, and flap-healing properties in vivo when used in the same dosage as in our study (Dos Santos et al 2006;Bagdas et al 2013Bagdas et al , 2014. In addition to systemic administration, long-term use of CGA has been studied to prove its bioactive capability in different models (Bagdas et al 2013(Bagdas et al , 2014Hunyadi et al 2012;Karthikesan et al 2010a, b).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…There has been a wide range of dosage for systemic administration of CGA, from 2.5 to 400 mg/kg (Hunyadi et al 2012;Karthikesan et al 2010a, b;Mubarak et al 2012;Yun et al 2012). However, systemic CGA treatment has antiinflammatory, analgesic, and flap-healing properties in vivo when used in the same dosage as in our study (Dos Santos et al 2006;Bagdas et al 2013Bagdas et al , 2014. In addition to systemic administration, long-term use of CGA has been studied to prove its bioactive capability in different models (Bagdas et al 2013(Bagdas et al , 2014Hunyadi et al 2012;Karthikesan et al 2010a, b).…”
Section: Discussionmentioning
confidence: 65%
“…The authors showed that topical application of CGA can accelerate the process of excision wound healing by its ability to increase collagen synthesis through upregulation of key players such as tumor necrosis factoralpha and transforming growth factor-beta1 during wound healing as well as by its anti-oxidant potential (Chen et al 2013). Similarly, topical or systematic CGA application in skin flap surgeries can accelerate healing and flap survival (Ashoori et al 1994;Bagdas et al 2014). Additionally, extracts from Turkish Scorzonera species, which contains high amounts of CGA, displayed wound-healing effect in incisional and excisional wound models (Kupeli Akkol et al 2011;Suntar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations